RAJ AND THE RAJAS ([S.l.])
1 online resource
Keywords: The decline of the Mughal Empire, the political ascendency of the British East India Company, a number of revivalist powers (the Sikhs, the Marathas, the Rohillas, etc.), and a large number of Indian princely states, resulted in redrawing the political spaces across India. In the process, the minting rights of the titular Mughal king and of the neo-independent Indian princely rulers were severely curbed by the dominant colonial power, both for political as well as economic reasons. The territorial expansion of the British Empire in India was invariably followed by the abolition of the native mints and the introduction of the imperial currency in the annexed territories. Indeed, the sikka' followed the flag. By presenting the monetary history of this period, this volume seeks to address some of the questions, viz. the effect of money supply on trade, prices of commodities and services, wage structures in different regions as well as on the administrative and military health of a political power. In this unique anthology, published studies along with unpublished archival records have been integrated into an overall theme. Together with a comprehensive bibliography-cum-list for further readings this volume is aimed to serve as a veritable reference tool.